Effect of the methylenetetrahydrofolate reductase 677C→T mutation on the relations among folate intake and plasma folate and homocysteine concentrations in a general population sample - de Bree, Angelika; Verschuren, WM Monique; Bjørke-Monsen, Anne-Lise; van der Put, Nathalie MJ; Heil, Sandra G; Trijbels, Frans JM; Blom, Henk J (The American journal of clinical nutrition, 2003)
Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme in folate and homocysteine metabolism. The common MTHFR 677C-->T polymorphism decreases the enzyme's activity. The objective of the study was to assess the effect of the polymorphism on the relations among folate intake, plasma folate concentration, and total plasma homocysteine (tHcy) concentration. The design was a cross-sectional analysis in a random sample (n = 2051) of a Dutch cohort (aged 20-65 y). At a low folate intake (166 micro g/d), folate concentrations differed significantly among the genotypes (7.1, 6.2, and 5.4 nmol/L for the CC, CT, and TT genotypes, respectively; P for all comparisons < 0.05). At a high folate intake (250 microg/d), folate concentrations in CT and CC subjects did not differ significantly (8.3 and 8.6 nmol/L, respectively, but were significantly higher (P = 0.2) than those in TT subjects (7.3 nmol/L; P = 0.04). At a low folate concentration (4.6 nmol/L), TT subjects had a significantly higher (P = 0.0001) tHcy concentration than did CC and CT subjects (20.3 compared with 15.0 and 14.1 micromol/L, respectively), whereas at a high folate concentration (11.9 nmol/L), the tHcy concentration did not differ significantly between genotypes (P > 0.2; <13.1 for all genotypes). The relation between folate intake and tHcy concentration had a pattern similar to that of the relation between plasma folate and tHcy concentrations. At any folate intake level, TT subjects have lower plasma folate concentrations than do CT and CC subjects. Yet, at high plasma folate concentrations, tHcy concentrations in TT subjects are as low as those in CT and CC subjects.